Configurational Theorizing and Multiple Theories in the Pursuit of Theoretical Advancement: A Systematic Review - Medina Molina, Cayetano; Pérez-Macías, Noemí; Rey-Tienda, Sierra (JOINETECH, 2025)
The objective and significance of the study. The inherent complexity of social phenomena has resulted in a notable increase in the utilization of the configurational approach for their study. Adopting a configurational perspective has consequences for both the development of theories and the analysis of data. In the first case, it involves the use of multiple theories as a means to more comprehensively explain the phenomena under investigation. Secondly, it concerns the implications of integrating different theoretical perspectives into the propositions established within the studies.The methodology used. In light of the contributions of two publications that have delineated the integration of theoretical multiplicity from a configurational perspective, the present study undertakes a systematic literature review encompassing the period from 2020 to 2025.Key findings. This study aims to identify the main contributions made by the academic literature in recent years. The identified studies emphasize the efficacy of theoretical multiplicity as a holistic perspective that facilitates the analysis of complex phenomena.Study limitations. This work has limited the search to Scopus, and can be extended to other repositories as well as different types of work beyond articles.Practical value of the findings. Furthermore, the potential of QCA as an analytical method is emphasized, as it is predominantly employed in studies that integrate multiple theories into the formulation of their propositions.
Keywords: Theoretical Multiplicity; Configurational Theorizing; Theory Synthesis; Configurational Multiplicity